Characteristics of growth and development of Stevia in field conditions and accumulation laws of glycosides in the leaves of plants (Experimental biology, 2015)
The results for the study of the growth and development of Stevia in the field, as well as patterns of accumulation of glycosides in the leaves of Stevia. The growth and development and accumulation of glycosides in the leaves of Stevia depends on environmental conditions and the type of line (latifolia, angustifolia and oval folia) of Stevia. Thetotal savings amount glycosides was 19-22, 5%, and the amount of 7.5-9% rebaudioside. The comparison between the amount of lines glycosides and rebaudioside was higher in the leaves of the latifolia stevia, the average value of the angustifolia stevia, far below the of the oval folia stevia.
Keywords: stevia; stevioside; glycoside; growth; developmen